The level of political conservatism of barangay officials of Dulag, Leyte. - Caminong, Leah, et al; Estil, Sheikha Kaye C. (Leah Caminong, 2010)
Dulag is a third-class municipality, dominated by Roman Catholics. Given this, it is a rural community which may have difficulty in accepting liberal ideas and change in political values. Hence, it is a very ideal locale for the study of political conservatism. Political conservatism refers to the extent of one's resistance to political changes, thus, characterized by traditionalism, pragmatism, property, hierarchy and authority.